2023
DOI: 10.1039/d3dt01643a
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of human telomeric unit TTAGGG and a photoactivatable Pt(iv) anticancer prodrug

Jiafan Lin,
Jishuai Zhang,
Ziqi Ma
et al.

Abstract: The interaction of a photoactivatable diazidodihydroxido Pt(IV) prodrug, trans,trans,trans-[Pt(N3)2(OH)2(py)2] (py = pyridine; 1), with a hexamer straight human telomeric DNA unit sequence (5′-T1T2A3G4G5G6-3′, I) upon light irradiation was investigated by...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 45 publications
(128 reference statements)
1
2
0
Order By: Relevance
“…5,14–16,18 Usually, there are two pathways proposed during the photodecomposition of complex 1 : two single-electron donations from either of the two azides to produce trans -[Pt II (py) 2 ] 2+ , or one azide and one hydroxide ligand to produce trans -[Pt II (N 3 )(py) 2 ] + . 4,19 Our previous reports have shown a sequence-dependent photodecomposition mechanism of complex 1 when incubating with DNA, 9,15–17 and the results obtained herein further confirmed such a photo-interaction mode of complex 1 . Moreover, the mono-functional trans -[Pt II (N 3 )(py) 2 ] + and bi-functional trans -[Pt II (py) 2 ] 2+ will produce distinct DNA adducts, e.g.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…5,14–16,18 Usually, there are two pathways proposed during the photodecomposition of complex 1 : two single-electron donations from either of the two azides to produce trans -[Pt II (py) 2 ] 2+ , or one azide and one hydroxide ligand to produce trans -[Pt II (N 3 )(py) 2 ] + . 4,19 Our previous reports have shown a sequence-dependent photodecomposition mechanism of complex 1 when incubating with DNA, 9,15–17 and the results obtained herein further confirmed such a photo-interaction mode of complex 1 . Moreover, the mono-functional trans -[Pt II (N 3 )(py) 2 ] + and bi-functional trans -[Pt II (py) 2 ] 2+ will produce distinct DNA adducts, e.g.…”
Section: Resultssupporting
confidence: 86%
“…9,15,18 Our recent research has shown that a 1,3-intrastrand crosslink at G4 and G6 might be formed by trans -[Pt(py) 2 ] 2+ in the photo-interactions of complex 1 with the 6-mer human telomeric unit, 5′-T 1 T 2 A 3 G 4 G 5 G 6 . 17 However, for adenine and cytosine, no explorations have been performed to investigate their potential to form crosslinks by complex 1 so far.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation